Profitability, Resource Use Efficiency and Marketing of Potato in East Siang Districts of Arunachal Pradesh, India - Hatai, Lakshmi Dhar (International Journal of Bio-resource and Stress Management, 2022)
The present study was undertaken with a sample size of 90 potato growers of East Siang district of Arunachal Pradesh State, India through stratified random sampling during 2019–20. The cost of cultivation was estimated based on cost concept. Cobb-Douglas production function was used as the better fit over linear form to find out the resource use efficiency of each variable input in potato production process. It was revealed that the total cost of cultivation on small, medium and large farms were Rs. 41604, Rs. 44150 and Rs. 44608 ha-1 respectively. Potato cultivation is highly labour intensive, as human labour contributes about 30% in Cost C3 (total cost). The gross return varied between Rs. 179914 ha-1 on large farms and Rs. 117927 ha-1 on small farms. The benefit-cost ratio varied between 3.16 to 5.63. There were many problems related to recurrent price fluctuation, high marketing, storage and transportation costs, inadequate storage facilities and lack of competitive marketing. For resource-use efficiency, the ratios of MVP to MFC were greater than one for human labour showing significant under-utilization of this resource and possibility of additional use to achieve the optimal level. Adoption of new production technology with sustained resources utilization can help farmers in minimizing the cost of production. In Arunachal Pradesh, the potato production and marketing can be improved by constructing the cold storage units in rural areas near production points, improving the market intelligence services and to make availability of the reliable information on processing and value addition, through small scale industries, FPOs and cooperatives.